"I Didn't Want to Be Ignorant": An Exploration of Why Preservice Teachers Sometimes Choose Silence in Critical Conversations About Texts With Elementary Children. (November 2021) - Diaz, Amanda R.; Schutz, Kristine M.; Woodard, Rebecca
Discussions about texts can offer valuable opportunities for critical conversations about power and privilege. While we know such conversations are important to have in school, many teachers report feeling unprepared to facilitate them. In an effort to understand the in-the-moment decisions preservice teachers (PSTs) make in response to children's contributions during critical conversations about texts, this qualitative, design-based study examines how PSTs responded to elementary-age children while facilitating discussions about texts in their field placements. Although various kinds of responses were made (e.g., eliciting children's thinking, orienting children's contributions to one another), in this analysis, we examine the moments where PSTs identified their silence as salient. Findings reveal that (1) some PSTs developing understanding of the role of talk and desire to efficiently accomplish the task did not seem to set them up to see critical conversations about texts as a space for sensemaking, and (2) other PSTs did see critical conversations about texts as spaces to engage in sensemaking but felt discomfort grappling with unanticipated issues that arose. We discuss implications for literacy researchers and teacher educators committed to supporting critical conversations with children in schools.